Evaluation of Phenotype-driven Variant Prioritization Methods for Cardiogenetic Diagnosis in the Brazilian Population - C. P. Bonetto, Manuela; S. Silva, Ed Carlos; José, Juliana; S. Rosa, Rogério; S. L. Patané, Jose (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2025)
We conducted a systematic benchmarking of four phenotype-driven variant prioritization methods–hiPhive, PhenIX, LIRICAL, and xRare–using validated diagnoses from a cohort of 164 Brazilian patients with cardiogenetic conditions. Each method integrated HPO-coded phenotypes and Whole-Exome sequencing data to rank variants by predicted clinical relevance. Performance was quantified using top-K recall metrics. Exomiser-based approaches (hiPhive and PhenIX) demonstrated superior overall performance, with PhenIX showing greater consistency across disease subtypes and hiPhive excelling in top-1 rankings. LIRICAL achieved high recall in specific conditions, while xRare had lower accuracy overall. These results support the potential of ensemble strategies to enhance diagnostic precision, particularly important in resourceconstrained healthcare settings like Brazil’s public health system.